What matters when asking, "what matters to you?" - perceptions and experiences of health care providers on involving older people in transitional care - Cecilie Fromholt Olsen; Jonas Debesay; Astrid Bergland; Asta Bye; Anne G. Langaas (BMC, 2020)
Abstract Background Transitional care for older chronically ill people is an important area for healthcare quality improvement. A central goal is to involve older people more in transitional care and make care more patient-centered. Recently, asking, "What matters to you?" (WMTY) has become a popular way of approaching the implementation of patient-centered care. The aim of this study was to explore health care providers' perceptions and experiences regarding the question of WMTY in the context of improving transitional care for older, chronically ill persons. Methods The data comprise semi-structured individual interviews with 20 health care providers (HCPs) who took part in a Norwegian quality improvement collaborative, three key informant interviews, and observations of meetings in the quality improvement collaborative. We used a thematic analysis approach. Results Three interrelated themes emerged from the analysis: WMTY is a complex process that needs to be framed competently; framing WMTY as a functional approach; and framing WMTY as a relational approach. There was a tension between the functional and the relational approach. This tension seemed to be based in different understandings of the purpose of asking the WMTY question and the responsibility that comes with asking it. Conclusions WMTY may appear as a simple question, but using it in everyday practice is a complex process, which requires professional competence. When seen in terms of a patient-centered goal process, the challenge of competently eliciting older people's personal goals and transferring these goals into professional action becomes evident. An important factor seems to be how HCPs regard the limits of their responsibility in relation to giving care within the larger frame of the patient's life project. Factors in the organizational and political context also seem to influence substantially how HCPs approach older patients with the WMTY question.